Innovation and industrial clusters - Vieira, Filipa Dionísio (2008)
On this case study the aim was to understand the mechanisms for knowledge acquisition and its transformation in innovation performance by Portuguese firms of the moulds industrial sector. Emphasis was put on the study of interactions between several external or internal elements of the system. Information obtained through intensive observation and study of eight firms of the moulds sector, all located in the region of Marinha Grande, in Portugal, allowed for the creation of an observation model of the moulds sector, in relation to the type of existing interactions between firms and between firms and other institutions. The study permits systematization and generalisation in the analysis of the innovative dynamics of this sector.